An Empirical Study on Pupils’ Knowledge on Active Volcanoes and Protective Measures in Ecuador - Otto, Karl-Heinz; Toulkeridis, Theofilos; Zach, Imme; Edler, Dennis (Journal of Geography Education, 2019)
This paper discusses the results of an extensive empirical study on students’ knowledge on volcanoes and volcanism in Ecuador, a country characterized by the highest density of high-risk volcanoes worldwide. The first part of the study deals with students’ knowledge on active volcanoes and protective measures against disasters. The study emerged from a research cooperation of the Geography Department of the Ruhr-University Bochum, Germany, and Departamento Ciencias de la Terra y Construcción of Universidad de Las Fuerzas Armadas (Sangolquí, Ecuador). The sample included two groups of participants: 1) fifth-graders and sixth-graders from the German schools in Quito and Guayaquil with no formal instruction on volcanoes and volcanism, 2) twelfth-graders attending the same schools.